Penanaman Nilai-Nilai Pendidikan Karakter dalam Kitab Ta’lim Muta’allim Karya Syekh Az-Zarnuji - Tyas Hidayatulloh; Abdul Hadi; Muhammad Hambal Shafwan (Dinasti Review, 2024)
The background of this research is that education is a learning process aimed at enhancing intellectual potential by providing it with correct knowledge, but this process also aims at character development efforts. However, education merely turns the seeker of knowledge into a knowledgeable person, without harmonizing it with good morals and ethics. The question raised in this research concerns the cultivation of character education values ??found in the book of thoughts by Sheikh az-Zarnuji, Talimul Muta’alim. The purpose of this research is to identify and investigate the character education values ??written in the book